The importance of utilizing supplementary vocabulary material in formative and summative assessment of reading comprehension: a study on Iranian upper intermediate EFL learners - Moradi, Elahe; Ghabanchi, Zargham (Penerbit Universiti Kebangsaan Malaysia, 2019)
Vocabulary knowledge and its role in reading comprehension is one of the main areas of focus in language research for the recent years. Knowledge of vocabularies as the building blocks of language has a very essential role. Without recognizing the meaning of words it would be impossible to produce and comprehend language. The aim of this study was to examine the impact of utilizing supplementary vocabulary material on improving the scores of reading comprehension course among Iranian upper intermediate EFL learners. To fulfill this objective, 80 males and female upper intermediate EFL learners were selected based on availability sampling. The level of students was determined through administering an Oxford Quick Placement Test (OQPT). The participants were divided into experimental and control groups. Both groups were pretested through a TOEFL reading comprehension test. In contrary to the experimental group that received supplementary vocabulary, the students in control group did not receive any supplementary materials. Then, during 21 sessions of treatment, three formative tests were used and in the last session the posttest (summative one) was administered to both groups. Descriptive statistics, covariance analysis, Kolmogrov-Smirnov test, and Levene’s test of equality of error variances were run to analyze the data. The findings revealed that utilizing supplementary vocabulary material had significant effect on reading comprehension scores. Also, the experimental group significantly outperformed the control group (p < .05) more on the summative assessments than the formative ones. Furthermore, the results indicated that female students had better scores compared to male students and they benefited more by utilizing supplementary vocabulary material in EFL upper intermediate reading comprehension classroom.